Awareness and preference in utilizing primary health-care services from rural health center as first point-of-care: A community-based cross-sectional study in South India - Arulprakash Sivanandan; S Ganesh Kumar; Yuvaraj Krishnamoorthy (Wolters Kluwer Medknow Publications, 2020)
BACKGROUND: First point-of-care (FPC) at the primary health care (PHC) level is an important public health issue at the global level. Patients directly come to tertiary health centers without a referral. AIMS AND OBJECTIVES: Hence, the current study was done to assess the proportion of individuals availing health-care services from rural health center (RHC) as FPC and reasons for not availing it. METHODS: A community-based cross-sectional study was conducted in Puducherry, coastal South India, among 367 households with 1510 individuals. Sociodemographic details, recent FPC during the past 6 months, morbidity profile, and reasons for not seeking were collected from all the individuals. RESULTS: About 44.5% (672/1510) of individuals used any health facilities, of which 70.4% (473/672) used RHC as the FPC. About 33.2% of individuals had a respiratory illness, 22.3% had general signs and symptoms. About 24.6% (32/130) mentioned the reasons for not seeking care as lack of appropriate health facilities. CONCLUSION: More than one-fourth of the study population not utilized services at PHC level. Improving the health facilities may help to increase these services.